2005
DOI: 10.1158/0008-5472.can-05-2754
|View full text |Cite
|
Sign up to set email alerts
|

Motexafin Gadolinium and Zinc Induce Oxidative Stress Responses and Apoptosis in B-Cell Lymphoma Lines

Abstract: There is an emerging appreciation of the importance of zinc in regulating cancer cell growth and proliferation. Recently, we showed that the anticancer agent motexafin gadolinium (MGd) disrupted zinc metabolism in A549 lung cancer cells, leading, in the presence of exogenous zinc, to cell death. Here, we report the effect of MGd and exogenous zinc on intracellular levels of free zinc, oxidative stress, proliferation, and cell death in exponential phase human B-cell lymphoma and other hematologic cell lines. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 52 publications
1
50
0
Order By: Relevance
“…Potentially interesting options in this respect are electron-affinic compounds such as motexafin gadolinium, which increases oxidative stress, enhances expression of metal response element-binding transcription factor-1-regulated genes, including MT, and can induce cell-cycle arrest and apoptosis in B-cell lines in vitro under appropriate conditions. 37 Since cells may be more susceptible if already subjected to oxidative stress, both the MT high DLBCL described in this report and the recently identified so-called OxPhos consensus cluster of DLBCL, characterized by increased levels of several genes associated with oxidative phosphorylation, 17 could constitute interesting targets for future investigations in clinical trials.…”
Section: Discussionmentioning
confidence: 87%
“…Potentially interesting options in this respect are electron-affinic compounds such as motexafin gadolinium, which increases oxidative stress, enhances expression of metal response element-binding transcription factor-1-regulated genes, including MT, and can induce cell-cycle arrest and apoptosis in B-cell lines in vitro under appropriate conditions. 37 Since cells may be more susceptible if already subjected to oxidative stress, both the MT high DLBCL described in this report and the recently identified so-called OxPhos consensus cluster of DLBCL, characterized by increased levels of several genes associated with oxidative phosphorylation, 17 could constitute interesting targets for future investigations in clinical trials.…”
Section: Discussionmentioning
confidence: 87%
“…Anticancer compounds such as nanoparticles and chemotherapeutic agents cause malfunction of mitochondria, which in turn induce cell death in a variety of cancer cells. 34,40,57 Previously, several studies have suggested that a variety of chemotherapeutic agents such as HDACIs, 58 redox cycling agents, 59 proteasome inhibitors, 60 and silver and graphene nanoparticles induce oxidative stress in the cells and eventually lead to cell death. 34,48,61 To examine the change in intracellular ROS level caused by oxidative stress, SKOV3 cells were treated with rGO-Ag (0.20 µM) alone, TSA (0.20 µM) alone, or …”
Section: Rgo-tsa and Tsa Enhance Production Of Rosmentioning
confidence: 99%
“…Several anticancer drugs have been shown to increase reactive oxygen species, including doxorubicin, mitomycin C, arsenic trioxide, and motexafin-gadolinium, which may contribute to their antitumor activity (43,44). Apparently, an increase in reactive oxygen species contributes to the antitumor activity of imexon, although this may not be the major mechanism.…”
Section: Discussionmentioning
confidence: 99%